Control of Protein Synthesis in Escherichia coli: Analysis of an Energy Source Shift-Down - Johnsen, Knud (1977)
The energy source shift-down described in the preceding paper (Molin et al., J. Bacteriol. 131: 7–17, 1977) was used to study the effects of shift-down on protein synthesis. The overall rate of protein synthesis was reduced immediately, and to the same extent, in stringent and relaxed strains. The primary effect of the shift was a slowing down of the polypeptide chain growth rate, a finding not previously reported. In stringent strains the normal, preshift rate was reestablished within 2 to 3 min, whereas in relaxed strains the chain growth rate remained low for about 20 min before slowly returning to the normal value, which was reestablished some 50 to 60 min after the shift. Throughout this transition, the stability of messenger ribonucleic acid (mRNA) remained unchanged in both strains. We interpret these findings as evidence of the more rapid reduction of the mRNA pool in the stringent strain after shift-down: we believe that very soon after the shift, the stringent strain reduces its pool of mRNA and with it the number of ribosomes engaged in protein synthesis. In this manner the number of active ribosomes is adjusted to the availability of energy and carbon. The relaxed strain cannot rapidly reduce its mRNA pool, which thus remains large enough to engage a near-preshift number of ribosomes during a prolonged period; as a consequence its ribosomes must work at a reduced rate. The possibility that ppGpp is involved in the control of mRNA production is discussed. After shift-down, the initial part of β-galactosidase (the auto-α fragment) was produced at a higher rate than complete β-galactosidase in the relaxed strain, as expected when translation is impeded.